Functional mapping of Saccharomyces cerevisiae Prp45 identifies the SNW domain as essential for viability - Martinkova, Katerina; Lebduska, Pavel; Skruzny, Michal; Folk, Petr; Puta, Frantisek (Journal of biochemistry, 2002)
The essential gene product Prp45 (379 aa) of Saccharomyces cerevisiae is a highly conserved, but N-terminally abridged, ortholog of the human transcriptional coactivator SKIP, which is involved in TGFbeta, Notch, and steroid hormone signaling. We used a diploid strain harboring PRP45 deletion, which is inviable in the haploid, to test for complementation with the truncated versions of Prp45. The N-terminal half of the protein (aa 1 to 190), denoted as the SNW domain, was found sufficient to support the essential function. Interestingly, substituting the SNW motif itself with AAA was compatible with viability. GFP-tagged Prp45 was localized in nuclear "speckles" over a diffuse nuclear background. We further found that Prp45 activated the transcription of a reporter gene in S. cerevisiae when targeted to DNA. The observed effect relied in part upon the presence of conserved helical repeats and upon the highly charged C-terminal domain (pI = 11.3). Prp45, which lacks most of the binding motifs of the human ortholog, and whose N-terminal half is sufficient for supporting the growth of prp45 cells, might be helpful in elucidating the essential function of SNW/SKIP proteins.
Keywords: aktivace transkripce; transfekce; Saccharomyces cerevisiae Proteins; regulace genové exprese u hub; Plasmids; konzervovaná sekvence; Protein Structure, Tertiary; Transfection; fluorescenční mikroskopie; terciární struktura proteinů; Saccharomyces cerevisiae; reportérové geny; Conserved Sequence; Proto-Oncogene Proteins; Sequence Homology, Amino Acid; molekulární sekvence - údaje; Amino Acid Sequence; Transcriptional Activation; jaderné proteiny; peptidové mapování; sekvenční homologie aminokyselin; lidé; Microscopy, Fluorescence; Humans; Gene Expression Regulation, Fungal; Genetic Complementation Test; testy genetické komplementace; plazmidy; sekvence aminokyselin; Saccharomyces cerevisiae - proteiny; Molecular Sequence Data; Peptide Mapping; Genes, Reporter; Nuclear Proteins; protoonkogenní proteiny